Effect of Cholesterol and Equex-STM Addition to an Egg Yolk Extender on Pure Spanish Stallion Cryopreserved Sperm. (12th December 2013) - Gil, Lidia; Galindo-Cardiel, Iván; Malo, C.; González, N.; Álvarez, C.
Abstract : Cholesterol and Equex-STM are frequently added to different commercial and experimental extenders improving postthawing sperm quality. Doses of 125–150 mM of cholesterol from pig liver and 0.5–0.7% of Equex-STM were evaluated in a standard eggyolk extender (Martin et al., 1979). Six ejaculates per stallion from six pure Spanish stallions (6–8 years old) were collected in Martin's extender (B) and different mixtures of 125 mM-0.5% (I), 125 mM-0.7% (II), 150 mM-0.5% (III), and 150 mM-0.7% (IV) were added to original Martin's extender. Samples were frozen in 0.5 mL straws (100 × 10 6 spermatozoa) and thawed (21 s., 37 ∘ C water bath). After thawing the following parameters were evaluated: viability (V), motility (computer assisted sperm analysis, CASA; % nonprogressive NP; % progressive MP), hipoosmotic swelling test (HOST), acrosome integrity (A), fluorescence test (FL), and resistance test (RT). Sperm quality was significantly affected by stallion (in the parameters V, VI, NP, MP, HOST, A, FL, and RT), extraction (VI, NP, MP, HOST, A, and FL), and the different combinations of Equex-STM-cholesterol (FL). We concluded that 0.5% of Equex-STM mixed with 125 mM of cholesterol has obtained better sperm quality results than those of original Martin's extender, showing a simple and economic improvement of this home-made practical seminal extender.